Comparing the influence of mixed reality, a 3D viewer, and MRI on the spatial understanding of brain tumours - Fick, T.; Meulstee, J. W.; Köllen, M. H.; Van Doormaal, J. A. M.; Van Doormaal, T. P. C.; Hoving, E. W. (Frontiers in Virtual Reality, 2023)
Background: Multiple 3D visualization techniques are available that obviates the need for the surgeon to mentally transform the 2D planes from MRI to the 3D anatomy of the patient. We assessed the spatial understanding of a brain tumour when visualized with MRI, 3D models on a monitor or 3D models in mixed reality. Methods: Medical students, neurosurgical residents and neurosurgeons were divided into three groups based on the imaging modality used for preparation: MRI, 3D viewer and mixed reality. After preparation, the participants needed to position, scale, and rotate a virtual tumour inside a virtual head of the patient in the same orientation as the original tumour would be. Primary outcome was the amount of overlap between the placed tumour and the original tumour to evaluate accuracy. Secondary outcomes were the position, volume and rotation deviation compared to the original tumour. Results: A total of 12 medical students, 12 neurosurgical residents, and 12 neurosurgeons were included. For medical students, the mean amount of overlap for the MRI, 3D viewer and mixed reality group was 0.26 (0.22), 0.38 (0.20) and 0.48 (0.20) respectively. For residents 0.45 (0.23), 0.45 (0.19) and 0.68 (0.11) and for neurosurgeons 0.39 (0.20), 0.50 (0.27) and 0.67 (0.14). The amount of overlap for mixed reality was significantly higher on all expertise levels compared to MRI and on resident and neurosurgeon level also compared to the 3D viewer. Furthermore, mixed reality showed the lowest deviations in position, volume and rotation on all expertise levels. Conclusions: Mixed reality enhances the spatial understanding of brain tumours compared to MRI and 3D models on a monitor. The preoperative use of mixed reality may therefore support the surgeon to improve spatial 3D related surgical tasks such as patient positioning and planning surgical trajectories.